Role of Hematological Parameters in Predicting COVID-19 Disease Severity - Syeda Bint-E-Zahra, Jawad Zaffar Choudry, Hamid Iqbal, Huda Zameer, Zill-E-Rubab, Syed Tasadak Mehdi, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Nowadays there is a global crises due to the emergence and spread of corona virus (CoV-19). This is a life threatening problem at present as it causes the severe acute respiratory syndrome corona virus (SARS-CoV). Aim: To explore the value of changes in routine hematological parameters for prediction of COVID-19 disease severity among admitted patients. Study design: Experimental study. Methodology: Patients (n=222) having COVID-19 were enrolled. They were divided into two groups depending on the severity of disease. They were admitted into ITC and non-ITC. All patients underwent CBC and inflammatory markers. Various hematological markers were used as prognostic markers. Independent t-test and Chi square were applied and p value of <0.05 was taken significant. Results: Mean age for ITC patients was 49.40±16.26 while the mean age for patients with mild disease was 40.88±15.48. NLR was significantly increased in ITC patients (p value<0.0001). Among biochemical parameters, serum ferritin, CRP and LDH were significantly increased in patients with severe disease (p value<0.001). D-Dimers were elevated in 68.75% patients of group-A and 17% patients in group-B with p-value<0.0001. Conclusion: We concluded that NLR and d-Dimers are the best hematology parameters in order to predict severity of disease. Keywords: Covid-19, d-Dimers, NLR,NLM and Hematological Parameters.